Comprehensive analysis of 22 XPC polymorphisms and bladder cancer risk. - Sak, S; Barrett, J; Paul, AB; Bishop, D; Kiltie, A (2006)
Two major risk factors for bladder cancer are smoking and occupational exposure to chemicals. The XPC protein is crucial in the recognition and initiation of the nucleotide excision repair pathway which repairs the DNA adducts formed by carcinogens found in cigarette smoke and chemicals. Polymorphisms in the XPC gene have been shown to influence an individual's DNA repair capacity, and hence, increase that individual's susceptibility to cancer. We undertook a case-control study of 547 bladder cancer cases and 579 cancer-free controls to investigate the association between 22 XPC polymorphisms and bladder cancer susceptibility, and investigated gene-environment interactions. We showed that the nonsynonymous polymorphism Ala(499)Val was in strong linkage disequilibrium with two polymorphisms in the 3'-untranslated region (Ex15-184 and Ex15-177) with Lewontin's D' >or= 0.99 and r2 >or= 0.82. Individuals homozygous for the minor allele of Ala(499)Val, Ex15-184, or Ex15-177 had an increased risk of bladder cancer compared with those homozygous for the common allele [adjusted odds ratio (95% confidence interval), 1.65 (1.05-2.59), 1.82 (1.12-2.97), and 1.82 (1.12-2.96), respectively]. The associations were somewhat stronger for smokers and those occupationally exposed to chemicals, although tests for gene-environment interactions were not significant.